2003
DOI: 10.1200/jco.2003.09.103
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Intraocular Retinoblastoma With Vincristine and Carboplatin

Abstract: In combination with appropriate early intensive focal treatments, chemoreduction with vincristine and carboplatin, without etoposide, may be an alternative treatment for patients with early-stage intraocular retinoblastoma, although additional studies are needed. Patients with advanced intraocular disease require more aggressive treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 47 publications
1
95
2
2
Order By: Relevance
“…The series showed that carboplatin and vincristine or even carboplatin alone may achieve good tumor control. 12,[26][27][28] This new study shows that deescalation, using vincristine instead of etoposide, seems not enough active to achieve satisfactory tumor control and eye preservation without EBRT. Furthermore, the very low risks of etoposide-induced secondary leukemia (at the doses we used, only for the initial two courses) should not defer physicians from its use in this indication.…”
Section: Discussionmentioning
confidence: 99%
“…The series showed that carboplatin and vincristine or even carboplatin alone may achieve good tumor control. 12,[26][27][28] This new study shows that deescalation, using vincristine instead of etoposide, seems not enough active to achieve satisfactory tumor control and eye preservation without EBRT. Furthermore, the very low risks of etoposide-induced secondary leukemia (at the doses we used, only for the initial two courses) should not defer physicians from its use in this indication.…”
Section: Discussionmentioning
confidence: 99%
“…Even when combined with focal therapies, the triple drug combination is ineffective in as many as 40% of bilateral retinoblastoma patients (7). Moreover, etoposide has been found to increase the incidence of secondary malignancies likely due to DNA damage caused by this topoisomerase II inhibitor.…”
mentioning
confidence: 99%
“…Chemotherapy combined with laser treatment and cryotherapy has improved the eye salvage rate for children with bilateral retinoblastoma and preserved vision for some patients (7). However, latestage bilateral retinoblastoma remains difficult to treat with this approach (7). In addition, one of the drugs used to treat retinoblastoma worldwide (etoposide) is believed to be responsible for an increase in acute myeloblastic leukemia as a secondary malignancy (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapeutic agents such as carboplatin and etoposide, have been shown to effectively reduce the volume of intraocular tumours in children affected by retinoblastoma [74,75]. However, the toxicity of systemic chemotherapy, still represents an issue which deserves further investigation [76,77], particularly when genomic instability is involved, as in retinoblastoma [6,7].…”
Section: Current Chemotherapy For Retinoblastoma and High Doses Of VImentioning
confidence: 99%